Atividade experimental para o ensino de ondas estacionárias - Norbiato, Julio Cesar (2019)
This work proposes an educational product based on David Ausubel’s Signiﬁcant Learning Theory. It is based on the construction and application of an experimental set for the teaching of stationary waves in vibrating strings, as well as the suggestion of a didactic sequence for meaningful learning. As the experiment is applied at the beginning of the sequence, it has an investigative character. It is provided a theoretical review about mechanical waves, standing waves in strings and harmonic formation. Then, it is presented a list of materials used for the preparation of the experiment, with its description, where to acquire, and a script for the mounting of the experimental kit. After the experiment and data collection, the students make the graphs and the adjustment to obtain the relation between the frequency, linear density, traction force and length, for the interference of mechanical waves in a string. The experimental set was applied in the same classroom, of a Junior year high school class in a private school at Foz do Iguaçu city, in which the students involved approved and praised the way in which the content was approached. It is concluded that the educational product, due to its easy to construct, low cost and does not require a speciﬁc physics laboratory for its application, is feasible and can be applied in a way that contributes to meaningful student learning.